Pengaruh Penggunaan Shopeepayleter terhadap Perilaku Konsumtif pada Mahasiswa Universitas Bhinneka PGRI Tulungagung - Novitasari, Viola; Yanuari, Sri Wulan (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
One form of technological development, especially in the field of E-commerce, is the many payment features provided with various conveniences. Currently, online shopping is increasingly popular, especially such as ShopeePay, ShopeePaylater, bank transfers, COD, payments through Shopee partners and many more. With the availability of payment facilities that include special offers such as discounts, it can encourage students to engage in consumer behavior. Therefore, researchers are interested in conducting this study to determine the effect of using ShopeePaylater on the consumer behavior of students at Bhinneka PGRI Tulungagung University. This study is a quantitative study, with the population used being all students at Bhinneka PGRI Tulungagung University. The sample uses the Lameshow formula. Data collection techniques by distributing questionnaires or questionnaires. The results of partial data testing show that the use of ShopeePaylater (X) has a t-count value (16.933)> t-table (1.985) and a significance value of 0.000 <0.05. So it can be concluded that partially there is a negative influence of the use of ShopeePaylater on student consumer behavior. The Adjusted R2 value is 0.743, which means that ShopeePaylater influences student consumer behavior by 74.3%. While the remaining 25.7% is influenced by other factors not examined in this study such as: lifestyle and the influence of financial literacy.